CONCEPTUAL PARADIGMS OF STRATEGIC MANAGEMENT DEVELOPMENT: HISTORY AND CONTEMPORARY DIMENSIONS - Галушка, Зоя Іванівна (Riga, Latvia: Baltija Publishing, 2026)
It is noted that global instability, digital transformation, and the transition to a BANI environment reduce the effectiveness of traditional strategic management approaches. The article identifies key transformations in strategic management, including the shift from long-term planning to adaptive strategy, the growing importance of strategic resilience, digital technologies, artificial intelligence, big data, and integrated risk management. It is substantiated that flexible, network-based, platform-oriented, and ecosystem-based organizational forms enhance strategic adaptability and competitiveness. The research concludes that an adaptive, innovation-driven, and ecosystem-oriented paradigm of strategic management is emerging under conditions of global uncertainty.
Розділ у міжнародній монографії